Improving Pension Information: Experimental Evidence on Learning Using Online Resources - Vallette, P (Elsevier B.V., 2025)
Deciding what to do with one s pension funds is a high-stakes, one-shot decision. Retirement schemes are often described in technical jargon that few people understand. We consider whether the learning process can be eased by providing information in video format (vs. the standard textual format) and by changes to the user interface of the websites on which individuals learn about their pension options. The results of a field experiment with 50 to 70-year-old participants and a laboratory experiment with university students both indicate that videos are significantly and substantively more effective in increasing the number of correct responses to a retirement comprehension test. The effect of changing the format from text to video on the number of correct responses is comparable to the effect of a large improvement in financial literacy. The significance of this effect is robust to changes in the content of the videos, with equivalent impact in private and public pension schemes. The study is conducted in association with the Chilean pension authority (Superintendencia de Pensiones) and experts from the National Social Security Organization of Chile (Instituto de Previsión Social). © 2025
Keywords: Choice architecture; Financial literacy; Retirement decisions; User interface